Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : \(\frac{x-1}{3}=\frac{y-4}{6}=\frac{y-4-\left(x-1\right)}{6-3}\) \(=\frac{y-4-x+1}{3}=\frac{y-x-3}{3}=\frac{1}{3}\)
Nên : \(\frac{x-1}{3}=\frac{1}{3}\Rightarrow x-1=1\Rightarrow x=2\)
\(\frac{y-4}{6}=\frac{1}{3}\Rightarrow y-4=2\Rightarrow y=6\)
Vậy x = 2 ; y = 6
a, \(2x-3< 0\Leftrightarrow2x< 3\Leftrightarrow x< \frac{3}{2}\)
b, \(\left(2x-4\right)\left(9-3x\right)>0\)
\(\Leftrightarrow\hept{\begin{cases}2x-4>0\\9-3x>0\end{cases}\Leftrightarrow\hept{\begin{cases}x>2\\x< 3\end{cases}\Leftrightarrow2< x< 3}}\)
a. \(2x-3< 0\Leftrightarrow2x< 3\Leftrightarrow x< \frac{3}{2}\)
b. \(\left(2x-4\right)\left(9-3x\right)>0\Leftrightarrow18x-6x-36+12x>0\Leftrightarrow24x>36\Leftrightarrow x>\frac{3}{2}\)
c. \(\frac{2}{3}x-\frac{3}{4}>0\Leftrightarrow\frac{2}{3}x>\frac{3}{4}\Leftrightarrow x>\frac{9}{8}\)
d. \(\left(\frac{3}{4}-2x\right)\left(\frac{-3}{5}+\frac{2}{-61}-\frac{17}{51}\right)\le0\)
\(\Leftrightarrow\frac{3}{4}-2x\le0\Leftrightarrow2x\le\frac{3}{4}\Leftrightarrow x\le\frac{3}{8}\)
e. \(\left(\frac{3}{2}x-4\right).\frac{5}{3}>\frac{15}{6}\Leftrightarrow\frac{3}{2}x-4>\frac{3}{2}\Leftrightarrow\frac{3}{2}x>\frac{11}{2}\Leftrightarrow x>\frac{11}{3}\)
+) Nếu\(x\ge\frac{1}{2}\)thì \(\left|x-\frac{1}{2}\right|=x-\frac{1}{2}\)
\(\Rightarrow P=x-\frac{1}{2}+\frac{3}{4}-x=\frac{1}{4}\)(1)
+) Nếu \(x< \frac{1}{2}\)thì \(\left|x-\frac{1}{2}\right|=\frac{1}{2}-x\)
\(\Rightarrow P=\frac{1}{2}-x+\frac{3}{4}-x=\frac{5}{4}-2x\)
Mà \(x< \frac{1}{2}\Leftrightarrow2x< 1\Leftrightarrow-2x>-1\Leftrightarrow\frac{5}{4}-2x>\frac{1}{4}\)(1)
Từ (1) và (2) suy ra \(P\ge\frac{1}{4}\)
\(\Rightarrow P_{min}=\frac{1}{4}\Leftrightarrow x=\frac{1}{2}\)
Ta có :\(\left(\frac{3}{2}-\frac{5}{11}-\frac{3}{13}\right).\left(2x-2\right)=\left(-\frac{3}{4}+\frac{5}{22}+\frac{3}{26}\right)\)
=> \(\left(\frac{3}{2}-\frac{5}{11}-\frac{3}{13}\right).\left(2x-2\right)=-\frac{1}{2}\left(\frac{3}{2}-\frac{5}{11}-\frac{3}{13}\right)\)
=> \(2x-2=-\frac{1}{2}\)
=> \(2x=\frac{3}{2}\)
=> \(x=\frac{3}{4}\)
\(\Rightarrow\frac{x+15}{x}=\frac{4}{3}\Rightarrow3.\left(x+15\right)=4.x\Rightarrow3x+45=4x\Rightarrow4x-3x=0-45\Rightarrow x=-45\)